1970
DOI: 10.3126/kumj.v7i2.2711
|View full text |Cite
|
Sign up to set email alerts
|

Poisoning cases attending emergency department in Dhulikhel Hospital- Kathmandu University Teaching Hospital

Abstract: Objective: The objective of the present study is to evaluate the characteristics of acute poisoning cases admitted to emergency department over a one year period. The demographic, clinical and psycho-social aspects of the patients were analysed. Materials and methods: A hospital based study was carried out in the emergency department, Kathmandu University Teaching Hospital/ Dhulikhel Hospital, Dhulikhel analysing the data of the poisoning cases attended for one year. The study was carried out amongst inpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
44
4
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 5 publications
12
44
4
2
Order By: Relevance
“…OP poisoning is most common in 12-14 yrs except one 25 days of homicidal case and two children. OP was most common poisoning as reported by Maharattha SB et al and was the most abused substances in Orissa India as reported by SK Dash et al 5,4 Kerosene poisoning was most common in winter and spring poisoning cases were admitted to hospital, for periods ranging from 1-175 days, further confirming the high poisoning-related morbidity in this country. There were no mortality among 5 almunium phosphide poisoning in Bir Hospital.…”
Section: Totalsupporting
confidence: 51%
See 4 more Smart Citations
“…OP poisoning is most common in 12-14 yrs except one 25 days of homicidal case and two children. OP was most common poisoning as reported by Maharattha SB et al and was the most abused substances in Orissa India as reported by SK Dash et al 5,4 Kerosene poisoning was most common in winter and spring poisoning cases were admitted to hospital, for periods ranging from 1-175 days, further confirming the high poisoning-related morbidity in this country. There were no mortality among 5 almunium phosphide poisoning in Bir Hospital.…”
Section: Totalsupporting
confidence: 51%
“…Forty percent of our parents were laborer and farmers similar to Marahatta SB et al 40% farmers. 5 In our study 18 (60%) patients reached hospital emergency within three hour while 23 (77%) within 6 hours of the incident. In a similar study conducted at Bir Hospital by Singh DP et al 61.6% of patients reached hospital within three hours.…”
Section: Totalmentioning
confidence: 45%
See 3 more Smart Citations